Carcinoembryonic antigen is a sialyl Lewis x/a carrier and an E‑selectin ligand in non‑small cell lung cancer - Ferreira, Inês Gomes (2019)
LPCC/Pfizer 2011. Tagus TANK award 2018 (grant no. 1/2018). SFRH/BD/100970/2014 SFRH/BPD/108686/2015